Analysis of the lexical meaning of hitting in the Northern dialect of Malay - Sha'ri, Sharil Nizam; Abdul Aziz, Adi Yasran; Husain, Salina; Yop Othman, Zul Hanis (Asian Journal of Social Science and Management Technology, 2024)
The interpretation of lexical meaning especially in the Malay dialect has shown the ambiguity of the lexical meaning. This is because the user becomes confused in understanding the meaning of each lexical item that is spoken so that the user cannot accurately guess the meaning that is spoken. In this study, the researcher has studied the Northern dialect (DU) entries selected in the Kamus Dewan Fourth Edition (KD4) which have the problem of ambiguity in the interpretation of meaning. The focus of this study is to analyze DU entries that have ambiguity of meaning based on the definition of KD4 using the component analysis theory of meaning (1975) as well as to formulate new meanings that either have similarities or functional differences based on DU in KD4. The research methodology involves literature and field studies. The number of respondents was 30 people from the Federal Agricultural Marketing Authority (FAMA) located in Bandar Baru Selayang, Selangor. Interview and audio recording methods were used during the process of collecting research data. The results of the study found that there was a discovery of new meaning obtained from interviews with native speakers of DU. Thus, this study is expected to open space for future researchers that the study of lexical meaning, especially in dialects, still has many gaps to study.